Ambidexterity and organizational learning: revisiting and reconnecting the literatures. Issue 4 (13th May 2019) - Brix, Jacob
Abstract : Purpose: The purpose of the study is to investigate how the processes of exploration and exploitation have developed in parallel in the literature of organizational ambidexterity and organizational learning, since James March published his seminal paper in 1991. The goal of the paper is to provide a synthesis of exploration and exploitation based on the two areas of literature. Design/methodology/approach: The study is conceptual and no empirical data have been used. Findings: The study advances current understanding of exploration and exploitation by building a new model for organizational ambidexterity that takes into account multiple levels of learning, perspectives from absorptive capacity and inter-organizational learning. Originality/value: The study's novelty lies in the creation and discussion of a synthesis of exploration and exploitation stemming from organizational ambidexterity and organizational learning.